The Application of PDCA in the Quality Management of Classroom Teaching in "University Physics" - Zhenping Xie (Forest Chemicals Review)
In the study of the course "University Physics", the theoretical knowledge is strong, and the students’ learning foundation is inconsistent. This paper introduces the PDCA cycle model into the teaching, which helps to find the problems existing in the classroom teaching, and gives the construction strategy to continuously improve teaching effect.